건물의 활하중을 고려한 소형풍력발전시스템의 최대 설비용량 선정기법 - 이여진(Yeo-Jin Lee); 김성열(Sung-Yul Kim) (전기학회 논문지 P권, 65(3), 2016)
Due to environmental issues such as global warming, the reduction of greenhouse gas emissions has become an inevitable measure to be taken. Among others, the building sector accounts for 50% of total carbon dioxide emissions, which is significantly high. Therefore, in order to reduce carbon dioxide emissions of the buildings, improving the energy efficiency by utilizing wind power among renewable energy sources is recommended. In case of buildings in the planning stage, it is possible to take the load of wind power generation systems into consideration when determining installed capacity. Already completed buildings, however, should be connected to small wind electric systems according to the live loads of the buildings based on the architectural design criteria. In order to connect to a building that has already been completed, it is necessary to consider the load of the small wind electric system as well as the live load of building. In addition, we need to generate the maximum electricity possible by determining the maximum installed capacity in a small area. In this paper, we propose the method for determining maximum capacity for building integrated small wind electric systems, which takes into account the considerations associated with connecting small wind electric systems to completed buildings. This can be developed into a system linked to solar power, which makes it possible to improve the energy independence of the building. In addition, carbon dioxide reduction by improving energy efficiency is expected.